ICT IN DISTANCE LEARNING: TEACHERS’ ATTITUDES AND PROBLEMS - Aldha Williyan; . sirniawati (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
In 2020, conducting education in distance is obligatory since the education must continue while the world is still fighting with the coronavirus disease and one of the ways of teaching in distance learning is using ICT. While several studies have investigated teachers’ attitudes of using ICT in face to face classrooms, few studies investigate teachers’ attitudes of using ICT in distance learning. This study examines 52 teachers’ attitudes and problems in using ICT in EFL distance learning in a language development center. The questionnaires are delivered and the interview is conducted to collect the data that disclose the teachers’ attitudes and problems of using ICT in distance learning. After analyzing the data, the findings in this study indicate that the teachers have positive attitudes toward the use of ICT in distance learning. The problems that occur when using ICT in distance learning are further discussed and possible suggestions are presented.